High Serpin Family A Member 10 Expression Confers Platinum Sensitivity and Is Associated With Survival Benefit in High-Grade Serous Ovarian Cancer: Based on Quantitative Proteomic Analysis - Guo, Wenwen; He, Xue; Ni, Jing; Ma, Liya; Cheng, Xianzhong; Wang, Congyang; Chen, Xiaoxiang; Wang, Yan (Frontiers in Oncology, 2021)
This study aims to identify differentially expressed proteins related with platinum sensitivity and to find biomarkers for predicting platinum response and survival outcomes in patients with high-grade serous ovarian cancer (HGSOC). Eligible HGSOC patients were divided into platinum-sensitive and platinum-resistant groups according to platinum-free interval (PFI). Tissue protein lysates from tumor tissues were subjected to an in-solution tryptic digest followed by Tandem Mass Tag (TMT)-labeling of the resulting peptides and mass spectrometric analysis. Candidate proteins were identified using differential expressed protein and gene-set enrichment (GSEA) analyses, and confirmed by immunohistochemistry (IHC), and their survival relevance were evaluated in TCGA ovarian cancer cohort. The results showed that there was a significant difference of protein expression profiling between the two patient groups. In the GSEA model, a gene-set of 239 extracellular matrix (ECM)-related proteins was significantly enriched in platinum-sensitive group (NES=3.82, q < 10-5), and this finding was confirmed in TCGA ovarian cancer cohort. Interestingly, an ECM-related gene expression, serpin family A member 10 (SERPINA10), was identified to be significantly positively correlate with overall survival (OS) and progression-free survival (PFS) in TCGA ovarian cancer cohort (all p<0.05). IHC results demonstrated that HGSOC patients with high SERPINA10 expression had longer PFI than the patients with low SERPINA10 expression (9 months vs. 5 months, p=0.038), and the SERPINA10 expression had an AUC value of 0.758 (95%CI =0.612-0.905; p=0.005) to discriminated platinum-sensitive tumors from platinum-resistant group. In conclusion, the results suggested that SERPINA10 could be a promising biomarker for predicting the response and survival in platinum-based chemotherapy of HGSOC.